Biology Learning Research Trends Based on Quantitative Literacy to Improve Higher Order Thinking Skills: A Literature Review - Azzahra, Waliyyatu; Surtikanti, Hertien Koosbandiah; Riandi (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
Empowerment of higher-order thinking skills is one of the goals to be achieved in 21st century learning. Learning in biology has led to quantitative data that requires reasoning and analysis to understand it. This literature review aims to discover trends in quantitative literacy-based learning research to increase HOTS. The research method used is a systematic literature review of several reputable articles published in recent years through content analysis. Based on the 16 papers used in this review, it was found that there was a tendency to increase research variation in various methods. This study also shows that ecological material is the most widely used topic in research related to quantitative literacy, both at the high school and university levels. Concerning the findings of this study, several recommendations have been put forward for future research that underpins quantitative literacy as the main focus in increasing HOTS. Some of these recommendations include increasing the variety of types of research and choosing a more diverse biological topic.